Women's Entrepreneurship Model in the Koperasi Medan Tuntungan, Ladang Bambu, Sumatera Utara: Pengabdian - Hasrita Lubis; Ismail, Shafinar; Rahayu, Sri; Yusrita; Triastuti Kurnianingsih, Heny; Nasrullah; Muliati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Entrepreneurship Women who joined the organization of the Medan Tuntungan Micro, Small Medium Enterprises Producer Cooperative (UMKM) in Baru Subdistrict, Ladang Bambu Village, Tuntungan District, Medan City, Sumatra; this cooperative houses 53 female MSME members consisting of homemakers and teenagers. He was aged 21 years to 60 years. The members of this cooperative have 152 Micro, Small, and Medium Enterprises (UMKM) units with 42 types of businesses. This research uses a qualitative and quantitative approach with a focus on case studies to gain an in-depth understanding of the women's entrepreneurship model through the Medan Tuntungan Cooperative in Baru Village, Ladang Bambu Village, Medan Tuntungan District, Medan City, North Sumatra. In this article, we will discuss three business units as start-ups, namely the tape business group unit, sweet potato chips, and dry cakes. The raw material for tapai (pai tape) will then be written on an ongoing basis for other business units as a community service activity by the Faculty of Business Economics at the Islamic University of North Sumatra in collaboration with the Study Center of Universiti Teknologi Mara Malaysia. Community service is carried out for MSME groups in the areas of knowledge, skills, and behaviour in marketing, bookkeeping, Marketing, and business networking.